EFFECT OF BACTERIA BACILLUS PSEUDOFIRMUS AND FUNGUS TRICHODERMA REESEI ON SELF-HEALING ABILITY OF CONCRETE - Hana Žáková (Acta Polytechnica CTU Proceedings, 2019)
There are usually used inorganic substances for the strengthening of self-healing ability of concrete but some specific types of bacteria or fungi may also be considered for use. The bacteria’s ability to fill pores and micro-cracks was investigated on cylindrical concrete specimens with the diameter 55 mm and height 5 mm. Bacteria Bacillus pseudofirmus and fungus Trichoderma reesei was used for the experiment. The main objective of the experiment was to investigate, if it is possible to use Bacillus pseudofirmus and Trichoderma reesei for self-healing concrete. The results show, that it is more advantageous to use Bacillus pseudofirmus than Trichoderma reesei in alkaline environment. It is desirable to create the most ideal conditions for microorganism’s growth, as possible. Bacteria should have positive effect on self-healing ability of concrete. Any effect of fungus on self-healing ability of concrete wasn’t confirmed.